Post‐traumatic growth in stroke carers: A comparison of theories. (7th September 2013) - Hallam, William; Morris, Reg
<x xml:space="preserve">Abstract</x> Objectives This study examined variables associated with post‐traumatic growth (PTG) in stroke carers and compared predictions of two models of PTG within this population: the model of Schaefer and Moos was compared to that of Tedeschi and Calhoun (1992, Personal coping: Theory, research, and application. Westport, CT: Praeger, 149; 1998, Posttraumatic growth: Positive changes in the aftermath of crisis. Mahwah, NJ: Lawrence Erlbaum, 99; 2004, Psychol. Inq., 15, 1, respectively). Design A cross‐sectional survey design was employed. Methods Carers of stroke survivors (N = 71) completed questionnaires measuring PTG, coping style, social support, survivor functioning, age, and carer quality of life. Correlation, multiple regression, and mediation analyses were used to test hypotheses. Results All carers completing the PTG measure (N = 70) reported growth, but average scores differed from cancer carers (Chambers et al., 2012, Eur. J. Cancer Care, 21, 213; Thombre et al., 2010, J. Psychosocial Oncol., 28, 173). PTG was positively correlated with deliberate and intrusive rumination, avoidance coping, social support, and quality of life. Regression analysis showed that factors identified by Tedeschi and Calhoun (deliberate rumination, intrusive rumination, social support, acceptance coping, survivor functioning) accounted for 49% of variance in PTG, whereas those identified by Schaefer and Moos (active coping, avoidance coping, social support, survivor functioning, and age) accounted for only 21%. Rumination, especially deliberate rumination, explained most variance in PTG and mediated the effect of social support on PTG. Conclusions The findings add to the limited body of evidence suggesting that stroke carers experience growth. Deliberate rumination and social support are important in explaining growth, and the findings support the model proposed by Tedeschi and Calhoun over that of Schaefer and Moos. Statement of contribution What is already known on this subject? Literature on caring for stroke survivors focuses on negative outcomes (Ilse, Feys, de Wit, Putman, & de Weerdt, 2008) to the exclusion of positive outcomes such as post‐traumatic growth (PTG; Calhoun & Tedeschi, 1999). Studies of a variety of health conditions have demonstrated that PTG occurs in patients and carers after illness events and is associated with well‐being (Gangstad, Norman, & Barton, 2006; Helgeson, Reynolds, & Tomich, 2006; Kim, Schulz, & Carver, 2007). Exploratory studies and studies of benefit finding have shown that PTG occurs in stroke carers (Bacon, Milne, Sheikh, & Freeston, 2009; Buschenfeld, Morris, & Lockwood, 2009; Haley et al., 2009; Thompson, 1991), but there are no studies using standard instruments to assess PTG in this population. Moreover, current theories posit different explanations for PTG (Schaefer & Moos, 1992, 1998; Tedeschi & Calhoun, 2004), and there is a need for empirical tests (Park, 2010). What does this study add? This study extends knowledge by measuring PTG with a standard instrument in a sample of UK stroke carers and investigating associated variables. The study also compared the predictive power of the models of PTG proposed by Tedeschi and Calhoun (2004) and Schaefer and Moos (1992, 1998). PTG was found in UK stroke carers, but levels differed from cancer carers in other countries. Factors associated with PTG were identified; Tedeschi and Calhoun's model best predicted PTG. Deliberate rumination had a direct effect on PTG and also mediated the effect of social support. Deliberate rumination is a possible target for therapeutic interventions to enhance PTG.